A genetic model for absent chylomicron formation: mice producing apolipoprotein B in the liver, but not in the intestine. - Young, S G; Cham, C M; Pitas, R E; Burri, B J; Connolly, A; Flynn, L; Pappu, A S; Wong, J S; Hamilton, R L; Farese, R V, Jr (The Journal of Clinical Investigation, 1995)
The formation of chylomicrons by the intestine is important for the absorption of dietary fats and fat-soluble vitamins (e.g., retinol, alpha-tocopherol). Apo B plays an essential structural role in the formation of chylomicrons in the intestine as well as the VLDL in the liver. We have developed genetically modified mice that express apo B in the liver but not in the intestine. By electron microscopy, the enterocytes of these mice lacked nascent chylomicrons in the endoplasmic reticulum and Golgi apparatus. Because these mice could not form chylomicrons, the intestinal villus enterocytes were massively engorged with fat, which was contained in cytosolic lipid droplets. These mice absorbed D-xylose normally, but there was virtually no absorption of retinol palmitate or cholesterol. The levels of alpha-tocopherol in the plasma were extremely low. Of note, the absence of chylomicron synthesis in the intestine did not appear to have a significant effect on the plasma levels of the apo B-containing lipoproteins produced by the liver. The mice lacking intestinal apo B expression represent the first genetic model of defective absorption of fats and fat-soluble vitamins and provide a useful animal model for studying nutrition and lipoprotein metabolism. Images